Reading Between the Lines : Translation of Allusions in the Reading Challenge of RuPaul’s Drag Race All Stars - Myllyniemi, Amanda (My University, 2026)
This research examines how humorous insults containing allusions have been translated in the Finnish subtitles of RuPaul’s Drag Race All Stars, a reality competition programme featuring drag performers, and how those translation choices amount towards a successful insult. The data is analysed through Leppihalme’s (1997) allusion classes and translation strategies. Additionally, the research examines if the tone, humour, or meaning of the insults shifts or becomes unclear through translation. Furthermore, the research offers background information on the drag sociolect, the practise of humorous insulting also known as reading, and allusions. The research finds that the translation of surface-level meaning and tone was successful, whereas the translation strategies present in the data were not fully able to convey the multi-faceted allusions central to the lines, thus erasing a key part of their humour and meaning, and resulting in blunt, one-dimensional insults. The results underline the necessity of thorough knowledge of popular-, queer- and drag culture to ensure the most successful translations on the subject. As the data only displayed a narrow scope of Leppihalme’s (1997) strategies, research is necessary to further explore their full potential. Additionally, a larger set of data from the same programme would allow for more extensive, focused study of the translation of queer- and drag vocabulary.
Keywords: queer linguistics; sociolect; allusions; audiovisual translation; RuPaul’s Drag Race